2013
DOI: 10.1016/j.vetmic.2013.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Genetic dissection of complete genomes of Type 2 PRRS viruses isolated in Denmark over a period of 15 years

Abstract: Type 2 Porcine Reproductive and Respiratory Syndrome Virus (PRRSV) was first detected in Europe in 1996 co-incident with the introduction of a live attenuated vaccine. Since then, only limited ORF5 and ORF7 sequences of Type 2 PRRS viruses have been reported throughout Europe. In the present study, the genetic and antigenic diversity of 11 complete genomes and 49 ORF5 and 55 ORF7 nucleotide sequences obtained from 57 viruses in Denmark from 2003 to 2012 were examined. The genetic identity of the 11 complete ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 50 publications
3
22
0
Order By: Relevance
“…Both PRRSV-1, subtype 1 and PRRSV-2 are circulating and causing disease in some European countries [7,8]. In contrast, PRRSV-1 strains belonging to subtypes 2, 3, and 4 have never been detected in Western Europe [23].…”
Section: ⇑ Corresponding Authormentioning
confidence: 99%
“…Both PRRSV-1, subtype 1 and PRRSV-2 are circulating and causing disease in some European countries [7,8]. In contrast, PRRSV-1 strains belonging to subtypes 2, 3, and 4 have never been detected in Western Europe [23].…”
Section: ⇑ Corresponding Authormentioning
confidence: 99%
“…Assuming that sequence divergence occurred by independent mutations at a constant rate, a number of lineages appeared to have become established before PRRS was recognized in the late 1980s. Later inclusion of additional datasets into the system indicated that all major groups of type 2 PRRSV have been identified (Brar et al, 2011;Kvisgaard et al, 2013;Shi et al, 2013b).…”
Section: Phylogenetic Classification Of Type 2 Prrsvmentioning
confidence: 99%
“…All Danish isolates spanning a period of over a decade are in lineage 5, sublineage 5.1, which contains PRRS MLV (Bøtner et al, 1997;Kvisgaard et al, 2013;Nielsen et al, 2001). Sparse sequence data from Europe and Russia, primarily in Germany, Lithuania, Poland and Slovakia, shows that independent introduction of virulent field viruses in lineages 1 and 8 has also occurred.…”
Section: Type 2 Prrsv Diversity Dynamics: What's New?mentioning
confidence: 99%
See 1 more Smart Citation
“…26 Type 2 PRRSV has been reported sporadically in Europe, and most isolates share a high degree of identity with the modified live vaccine strain that is based on the type 2 VR2332 isolate. 15,19,26 On natural infection via the respiratory route, the virus has a specific tropism for cells of the monocyte-macrophage lineage. 7 After replication in local macrophages, the virus rapidly spreads to lungs and lymphoid organs.…”
Section: Introductionmentioning
confidence: 99%